أنموذج مقترح لتطوير أعمال التدقيق في إقليم كوردستان وفقاً لمعيار أنتوساي 1300 - Sheraz Ahmed Mustafa (Iraqi Journal for Administrative Sciences, 2024)
The research aims to achieve harmony and eliminate differences in the preparation and development of audit plans in the Office of Financial Supervision of the Kurdistan Region at all levels by applying the requirements of the No. (1300) standard issued by INTOSAI and international auditing standards and local evidence and laws and legislation, which requires the auditor to perform the audit process and make Due diligence and commitment to quality audit plans. The research is based on the main hypothesis that: The application of the requirements of Standard No. (1300) issued by INTOSAI, which is concerned with planning for the implementation of or alignment with oversight tasks by the oversight bodies affiliated with the FSA, positively affects the development, efficiency, and effectiveness of the SAIs' performance and the quality of their audit reports. One of the most important findings of the research is that during the course of its work the Bureau did not rely on any of the auditing standards, whether they are international, such as INTOSAI or regional standards such as Arbusai or Asusai standards, but it did not depend on Iraqi rules as well, and the Court's law did not refer to any of these criteria. The basis and the measurement that depends on him during the performance of his professional duties are the laws in force in the Kurdistan Region of Iraq.The research concluded several recommendations, the most important of which is to give more attention by the heads of the auditing bodies to all aspects of the planning process, including taking into consideration the importance of the relative importance and risks of the audit. As well as working to raise the bureau to the level of the international financial supervision agencies through participation in international workshops on the standards of the International Organization of Supreme Audit Institutions and INTOSAI.